Estimate of circRNAs and microRNAs synergies on clinical advance of psoriasis - Saleh, Amany A.; Tayel, Safaa I.; Shehata, Wafaa A.; El-Masry, Eman A.; Abd-Elhafiz, Huda I.; Elhelbawy, Mohammed G.; EL-Naidany, Sherin S. (Journal of immunoassay & immunochemistry, 2025)
Noncoding RNAs have recently proven their contributing role in the pathogenesis of numerous diseases. The etiology of psoriasis is still not well defined, and genetic and environmental factors are blamed. We meant to explore the association of circRNAs/microRNAs in psoriasis and inspect their correlation with the clinical features of the disease. This study included 166 subjects: 83 cases with plaque psoriasis and 83 age- and sex-matched healthy persons as the control group. The expression levels of circRNA000102, circRNA0045272, circRNA0084764, and microRNAs -93,181, 16a, and 21 were estimated by quantitative real-time PCR. CircRNA0045272 was ten-fold up-regulated, whereas circRNA0084764 and circRNA000102 were about two-fold downregulated in patients vs. control. MicroRNAs −93 and 181 were significantly downregulated in patients vs. control, whereas microRNA −16a and 21 were up-regulated in patients vs. control. CircRNA0045272 was positively correlated with microRNA 181, and circRNA0084764 was positively correlated with microRNA 93 and microRNA 181. CircRNA0045272 had the highest sensitivity (98.8%) and specificity (93.98%), and microRNA-16a had sensitivity (98.80%) with specificity (93.98%). We assume that circRNAs can predict psoriasis occurrence and progression by sponging a set of microRNAs and can modulate several genes that disturb immune cell balance and inflammatory elements in psoriasis.